2014
DOI: 10.1186/preaccept-9414691321834135
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to deltamethrin of wild and domestic populations of Triatoma infestans of the Gran Chaco and the Inter-Andean Valleys of Bolivia

Abstract: Background: The persistence of Triatoma infestans and the continuous transmission of Trypanosoma cruzi in the Inter-Andean Valleys and in the Gran Chaco of Bolivia are of great significance. Coincidentally, it is in these regions the reach of the vector control strategies is limited, and reports of T. infestans resistance to insecticides, including in wild populations, have been issued. This study aims to characterize the susceptibility to deltamethrin of wild and domestic populations of T. infestans from Boli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…This suggests that Andean populations have particular genetic backgrounds that enable the development of resistance to pyrethroid insecticides more rapidly than non-Andean populations. This is in according with Roca-Acevedo et al (2011), Depickere et al (2012, and Gomez et al (2014) who showed varying degrees of tolerance to deltamethrin and fipronil in the sylvatic T. infestans from Andean valleys of Bolivia. However, as has been seen in this review, the resistance to pyrethroid insecticides evolved in the Argentinean Chaco (i.e.…”
Section: Is There Any Association Between the Persistence Of T Infessupporting
confidence: 90%
See 2 more Smart Citations
“…This suggests that Andean populations have particular genetic backgrounds that enable the development of resistance to pyrethroid insecticides more rapidly than non-Andean populations. This is in according with Roca-Acevedo et al (2011), Depickere et al (2012, and Gomez et al (2014) who showed varying degrees of tolerance to deltamethrin and fipronil in the sylvatic T. infestans from Andean valleys of Bolivia. However, as has been seen in this review, the resistance to pyrethroid insecticides evolved in the Argentinean Chaco (i.e.…”
Section: Is There Any Association Between the Persistence Of T Infessupporting
confidence: 90%
“…Depeckire et al (2012) reported resistance to deltamethirn in five localities of Department of Santa Cruz (Estancia Bacilio, Kuatrienda, San Silvestre, Rancho Nuevo and Tamachindi, RRs from 3.8 to 8.3) and one locality of Villamontes, Department of Tarija (Taiguati, RR = 818). Recently, high resistance to deltamethrin was reported again in Villamontes (RR=129.1) and low resistance in Departments of Cochabamba and Santa Cruz (RR from 4.2 to 8.5) (Gomez et al, 2014). All studies cited above showed the highest levels of resistance to pyrethroid insecticides in southern Bolivia, in the Department of Tarija.…”
Section: Chronology Of Detection and Distribution Of The Resistant Focimentioning
confidence: 89%
See 1 more Smart Citation
“…The meeting of fi eld populations more susceptible than the SRL (25) (28) (30) (33) reveal the fragility of this criteria.…”
Section: Methodological Difficultiesmentioning
confidence: 99%
“…The populations that were indicative of resistance were subjected to dose response trials, revealing wide variation in susceptibility (RR 50 3.8-818.0). Gomez et al (30) assessed the susceptibility of 9 populations from Gran Chaco and the Inter-Andean valleys of Bolivia (5 wild populations and 4 domestic populations) to deltamethrin. The wild populations showed low variation in susceptibility (RR 50 0.62-4.24), whereas wide variation in susceptibility was detected for the domestic populations (RR 50 2.9-129.1).…”
Section: History Of Triatominae Resistance To Insecticidesmentioning
confidence: 99%